Development of Food Industry of Northern Bukovyna and Khotyn Region in the Interwar Period - Rusnak, Oleksandr (Yuriу Fedkovych Chernivtsi National University, 2022)
An important role in the economy of Ukraine today is played by the food industry, which leads to considerable interest in studying its development in some regions in previous times. However, the functioning of food enterprises in Northern Bukovyna and Khotyn region in the interwar period has not yet been the subject of a separate scientific study. An in-depth analysis of archival materials, official statistical reports, and a number of publications revealed that the food industry in the studied region at the beginning of the Romanian rule was represented by the flour, sugar, alcohol, dairy, and meat processing branches. At the same time, the food industry was best developed in Chernivtsi County. By the end of the 1930s, the number of enterprises in this industry in the region had increased significantly. The range of products produced by them has also diversified. In that time according to the main indicators of the industry’s development, Chernivtsi County stood out among the three counties of Northern Bukovyna and Khotyn region, and a significant part of its enterprises was located in the city of Chernivtsi.
Розвиток харчової промисловості Північної Буковини і Хотинщини у міжвоєнний період
Keywords: Northern Bukovyna, Khotyn region, interwar period, food industry